Math
 👍 0
 👎 0
 👁 25

 👍 0
 👎 0
posted by PsyDAG
Respond to this Question
Similar Questions

MAth
2+3m=17 7 6 10 5 use inverse operations to solve each equation. Explain each step and identify the propaty used to reach steps. 19=h/38 solve the equation : expiation each step and identify the property used to reach each step
asked by AABBCC on October 25, 2015 
MAth
2+3m=17 7 6 10 5 use inverse operations to solve each equation. Explain each step and identify the propaty used to reach steps. 19=h/38 solve the equation : expiation each step and identify the property used to reach each step
asked by AABBCC on October 24, 2015 
Math
Use inverse operations to solve each equation. Explain each step and identify the property to reach step 19 = h/3  8 Solve the equation. Explain each step and identify the property used to reach step. 0.6x + 0.8 = 1.4
asked by chap on October 31, 2017 
Math
Solve the equation. Explain each step and identify the property usedbto reach each step. 0.6x + 0.8 = 1.4
asked by Darkdream on January 18, 2018 
Math
Solve the equation. Explain each step and identify the property used to reach each step 0.6x+0.8=1.4 Please help me with this question.
asked by Jasmine on December 9, 2017 
Math
Solve the equation. Explain each step and identify the property used to reach each step. 0.6x + 0.8 = 1.4
asked by Anonymous on October 21, 2019 
Math
Use inverse operations to solve each equation. Explain each step and identify the property used to reach step. 19 = h/3  8
asked by Darkdream on January 18, 2018 
math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields
asked by Valerie on October 22, 2019 
Math 7 A
Note: For questions 5 and 6, remember to show all of the steps that you use to solve the problem. Be sure to use the text box where the question mark (?) first appears to show your mathematical work. You can use the comments field
asked by jesse on November 20, 2017 
math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
Help PLZ!!
consider the steps to simplify the expression. Which property is used to reach Step 3? Expression: 4 3 7 + 7 + (3 4 7 ) Step 1: = 4 3 7 + (3 4 7 ) + 7 Step 2: = 4 + ( 3 7 ) + (3) + ( 4 7 ) + 7 Step 3: = 4 + ( 3 7 ) + (
asked by Daya on August 30, 2017